ANALYSIS OF HYDRAULIC POWER REQUIREMENTS OF CONTINUOUS COLORING LINE AREA EXIT MACHINE - Rohman, Rohman; Ade Kristian; Jatira; Yadi Heryadi (Magister Teknik Mesin Universitas Pancasila, 2025)
In the metal processing industry, hydraulic system play a crucial role in supporting the operation of production machines such as cut shear, mandrel, and coil cart. These machines rely on hydraulic power to function efficiently and reliably. This study aims to analyze and calculate the pressure and optimal hydraulic power required for each machine in the exit area of the continuos coloring line (CCL). The methodology includes measuring actual hydraulic pressure based on variations in the thickness nada width of galvalume sheets as coil weights, followed by quantitative descriptive analysis. The result show that the hydraulic pressure required by the cut shear machine varies from 58,1 bar to 139,62 bar depending on sheet galvalume dimensions. The mandrel machine pressure ranging from 15,93 bar to 28,93 bar depending to weight coil,, while the coil cart needs between 21,30 bar and 38,70 bar depending to weight coil. The highest recorded pressure reached 207,25 bar when all machine operated simultaneously under maximum load, approaching the pump is maximum capacity of 210 bar. This indicates that the system operates at near-optimal levels but closes to its safety threshold, thus requiring technical attention to maintain system reliability.